Effect of Work Environment and Work Discipline on Employee Performance - I Putu Adi Septiawan; Komang Krisna Heryanda (Universitas Pendidikan Ganesha, 2020)
This study aims to examine the effect of (1) work environment and discipline on employee performance, (2) work environment on work discipline, (3) work environment on employee performance, and (4) work discipline on employee performance on CV Puspa. The research design used in this study is causal quantitative. The subjects of this research are employees at CV Puspa and the object is the work environment, work discipline and employee performance. The population in this research is 76 Puspa employees. All populations are made as observation units, therefore this study is included as population research. Data collected by questionnaire technique, then analyzed by path analysis. The results showed that, (1) work environment and discipline had a positive effect on employee performance, (2) work environment had a positive effect on work discipline, (3) work environment had a positive effect on employee performance, and (4) work discipline had a positive effect on performance employee at CV Puspa.